2018
DOI: 10.3390/nu10121861
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Feeding Practices in a Cohort of Italian Late Preterm Infants

Abstract: Limited data are available on complementary feeding in preterm infants, who show increased nutritional needs and are at risk of altered postnatal growth. The aim of this study was to investigate the timing and content of complementary feeding in a cohort of late preterm infants. We conducted a prospective, observational study, including mothers who had given birth to infants admitted to level I or II of care with a gestational age between 34 and 36 weeks. Mothers were contacted at 3, 6 and 12 months after deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 29 publications
3
34
3
1
Order By: Relevance
“…We also found that every week of pregnancy duration was associated with a decrease of 33% of odds of early introduction to solids. On the other hand, a study of late preterm infants from Italy showed that in most cases, infants were introduced to complementary foods within 4 and 6 months of postnatal age [38]. Currently, there is no specific recommendation about introducing complementary feeding in prematurely born infants; nonetheless, it should be considered due to increased nutritional requirements, and the possibility of delayed motoric development, feeding difficulties or respiratory compromise depending on gestational age or comorbid diseases [37].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that every week of pregnancy duration was associated with a decrease of 33% of odds of early introduction to solids. On the other hand, a study of late preterm infants from Italy showed that in most cases, infants were introduced to complementary foods within 4 and 6 months of postnatal age [38]. Currently, there is no specific recommendation about introducing complementary feeding in prematurely born infants; nonetheless, it should be considered due to increased nutritional requirements, and the possibility of delayed motoric development, feeding difficulties or respiratory compromise depending on gestational age or comorbid diseases [37].…”
Section: Discussionmentioning
confidence: 99%
“…After examining the full texts of the 40 retrieved papers, 14 were excluded, as 9 did not actually deal with CF and 5 reported data only about term infants, leading to 26 suitable studies [ 5 , 6 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Five additional papers were identified from the reference lists of included studies [ 33 , 34 , 35 , 36 , 37 ]; 31 studies were then included in the systematic review [ 5 , 6 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ,…”
Section: Resultsmentioning
confidence: 99%
“…Among these, there were six narrative reviews [5,14,15,22,27,32], one systematic review [13], two meta-analyses [11,33], one commentary [17], two recommendations [36,37] and one study protocol [31]. Among the remaining 18 trials, there were 14 observational studies [6,9,10,12,[18][19][20][21]24,[28][29][30]34,35], two randomized controlled trials (RCTs) [16,25] and two papers pooling data from different RCTs [23,26].…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations